The firm value and marketing intensity decision in conditions of financial constraint: A comparative study of the United States and Latin America - Palomino-Tamayo, Walter (2020)
With this first systematic review of specific literature about diaspora marketing, it was found that this emerging literature focuses mainly on opportunities related to trade, tourism, and the acculturation between countries with different languages in only one host country. This research contributes towards a greater understanding of diaspora buying behavior using the Construal Level Theory, specifically with regard to the purchase of nostalgic products and services in the broader international context of five host countries: Colombia, Peru, Chile, Ecuador, and Panama. Another contribution is the use of e-WOM metrics derived from advertising posts on Instagram. The results show that diaspora consumers in host countries that have higher levels of individualism, less masculinity, and are further geographically from their homeland seek to consume greater amounts of nostalgic products.